Parent Training and Therapy in Children with Autism - Alessandro Frolli; Antonia Bosco; Francesca Di Carmine; Antonella Cavallaro; Agnese Lombardi; Luana Sergi; Giulio Corrivetti; Maria Carla Ricci (MDPI AG, 2021)
With the introduction of the Diagnostic and Statistical Manual of Mental Disorders-5th ed. (DSM-5) autism spectrum disorders (ASD) fall into the category of neurodevelopmental disorders. ASD is characterized by the inhibitory mechanisms responsible for social adaptation and emotional expression being underdeveloped, causing a child's recognition and understanding of emotions to be impaired. Our study hypothesizes that early intervention using behavioral interventions such as Applied Behavior Analysis (ABA) and reflexive functions (RF) training on parents can improve the development of joint attention (JA), a cognitive precursor to the theory of mind (ToM) and mentalization processes. We considered a sample of 84 children aged between 20 and 30 months who had received a diagnosis of risk of autism spectrum disorder (level 1). The sample was divided into two groups of 42 subjects, in the first group we carried out a weekly behavioral parent training (PT) based only on ABA principles, while in the second group we carried out a weekly PT aimed at improving reflective functions and parental awareness according to a model inspired by the model based on emotional mirroring and mentalization of Fonagy. Our study shows that parents who are able to make sense of both their own mental state and that of their child can serve as a protective factor for the child's development even in atypical developmental situations such as in ASD.